Last instar larva of Penepodium dubium (Hymenoptera: Sphecidae) - Christiano Buys, Sandor (Universidad de Costa Rica, 2001)
The last instar larva of Penepodium dubium is described from southeastern Brazil. This is the first description of an immature stage of the genus Penepodium. The larva of P. dubium is similar to those of Podium, but it can be distinguished from the species of this genus by the presence of depressions on the front and clypeus, and lack of brownish blotched areas on the head. The cocoon of Penepodium seems to be unique among those of Sceliphrini in bearing a nipple-like projection at one end.